The Dominance of Women in Structural Positions: A Gender Analysis of The Gowa Regency Education Office - Hastira, Muh Fichriyadi; Patty, Alberto Noviano; Jefri, Jefri; Burhan, Reksa; Pratama, Galank (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2024)
This research focuses on women who dominate structural positions in the Education Office of Gowa Regency, South Sulawesi Province. This study analyzes why women hold more structural positions than men at the Education Office of the Gowa Regency. I also explained how gender identification is used to place structural positions at the Education Office of the Gowa Regency. This research is qualitative and has a case study. Data was obtained through direct interviews with informants, namely the head of the Gowa Regency Education Office, the Regional Personnel Agency, and the Gowa Regent. The existing data were analyzed using triangulation analysis techniques between data obtained from interviews. The results of this study found that two factors cause the dominance of women in structural positions; the first is normative factors, including regulations related to gender mainstreaming and work experience, and the second is political factors, including the interests of the local government of Gowa Regency. This reveals that gender identification is no longer the leading indicator; positions are given based on ability and expertise, and thus, men and women have the same opportunities or access.